Modern treatment approaches to adult acute T-lymphoblastic and myeloid/T-lymphoblastic leukemia: from current standards to precision medicine. Issue 6 (26th November 2022) - Leoncin, Matteo; La Starza, Roberta; Roti, Giovanni; Pagliaro, Luca; Bassan, Renato; Mecucci, Cristina
Abstract : Purpose of review: To review the most recent advancements in the management of adult T-cell acute lymphoblastic leukemia (T-ALL), we summarize insights into molecular diagnostics, immunotherapy, targeted therapy and new techniques of drug sensitivity profiling that may support further therapeutic progress in T-ALL subsets. Recent findings: With current induction/consolidation chemotherapy and/or risk-oriented allogeneic stem cell transplantation programs up to 95% adult T-ALL patients achieve a remission and >50% (up to 80% in adolescents and young adults) are cured. The group of patients who fail upfront therapy, between 25% and 40%, is enriched in high-risk characteristics (unfavorable genetics, persistent minimal residual disease) and represents the ideal setting for the study of molecular mechanisms of disease resistance, and consequently explore novel ways of restoration of drug sensitivity and assess patient/subset-specific patterns of drug vulnerability to targeting agents, immunotherapy and cell therapy. Summary: The emerging evidence supports the contention that precision medicine may soon allow valuable therapeutic chances to adult patients with high-risk T-ALL. The ongoing challenge is to identify the best way to integrate all these new data into the therapeutic path of newly diagnosed patients, with a view to optimize the individual treatment plan and increase the cure rate.